O10 Person centred simulation: evaluating a multidisciplinary community educator training. (5th November 2017) - Hamilton, C; Clarkson, G; Oborne, S
Abstract : Background: The Health and Social Care Act 2012, imposes a legal duty for NHS England and clinical commissioning groups (CCGs) to involve patients in their care. Working synergistically with patients and simulated patients (SPs) produces the 'highest fidelity' learning experience. SPs in community roles are the patient proxy and advocate, where the needs, circumstances and preferences of the individual receiving care are paramount. We aimed to provide training for community educators to work effectively with SPs in the delivery of person centred simulation. Working collaboratively with community trusts and CCGs, fifteen educators from various professional groups participated. We aimed to ensure that the training was relevant, safe, meaningful and transferable complying with the ASPiH Standards. Project Description: A fourteen hour module was developed by simulation experts who sought input from: nurse specialists, complaints teams, chaplaincy, medical consultants, care-home managers, voluntary sector, care-givers, patients and relatives. SPs co-facilitated and role played; a lay observer attended. The principles of person-centred care¹ underpinned the module: * Affording people dignity, compassion and respect. * Coordinating personalised care, support or treatment. * Supporting people to recognise/develop their own strengths and abilities by linking the learning outcomes to the evaluation, we aimed to establish if the training was effective, achieving its objectives. We wanted to move from the traditional Likert scale, to evaluating in a way that captures self-assessed changes that occur as a result of the module; thus illustrating impact. Outcomes: Qualitative data was collected through filmed feedback from participants, the lay observer, SPs and facilitators. Quantitative data was collected at the end of the module through a retrospective pre-test/post-test. This reduced the "response shift bias"² of a conventional pre-test/post-test evaluation which encourages inaccurate self-report of self-assessed knowledge. All participants indicated higher agreement with every statement post module. The overall average for the six outcomes increased from 2.1 to 4.3. Participants were least confident in their ability to plan structured training sessions. This performance standard retained the lowest mean confidence after the workshop; mean level of agreement increased from 1.8 to 4.0. Engaging with SPs in a training session was an area where most gain was noted, 2.4. The participants' confidence had the highest mean level of agreement at 4.5. Conclusion: This is a highly transferable and replicable training. With ongoing support, community educators can become leaders in person centred simulation. Support would include: scenario/lesson-plan critique, observation, service users/health care team links and evaluation techniques. References: . The Health Foundation. Helping measure person-centred care 2014. www.health.org.uk/sites/health/files/HelpingMeasurePersonCentredCare.pdf . Howard GS, Dailey R. J of Applied Psychology April 1979;64(2):144–150.